Assessing the Impact of the Non-Physical Laboratory Approach on Open-Ended Environmental Laboratory Practice (Asean Journal of Engineering Education, 2025)
This study evaluates the impact of integrating virtual/online open-ended laboratories (OEL) into environmental engineering courses for undergraduate civil engineering students. Incorporating OEL allows students to engage in hands-on, problem-based learning activities that simulate real-world environmental challenges. This article focuses on the benefits, design considerations, and implementation strategies for integrating open-ended environmental laboratories into the undergraduate civil engineering curriculum, enhancing students' critical thinking, teamwork, and ability to develop sustainable engineering solutions. The study examines the implementation of problem-based laboratory techniques over four consecutive cohorts (n=229), capturing the transition from traditional OEL to fully online OEL during the COVID-19 Movement Control Order (MCO) and partially at subsequent post-pandemic conditions. Despite an initial decline in student learning performance during the first year of online OEL, subsequent years showed significant improvement. This trend aligns with student perception surveys, which reflect positive outcomes from the online OEL experience. One of the positive outcomes observed was the adaptability to future challenges. The experience of adapting to online learning environments prepared students for future professional scenarios that may require remote collaboration and virtual problem-solving. A notable insight from the partially online laboratory courses is the expanded opportunity to explore interactive virtual lab platforms and utilize remote data collection methods, enriching the teaching paradigm. Integrating open-ended laboratories in environmental engineering aligns with the Sustainable Development Goals (SDGs) and equips students with essential skills to address global sustainability challenges effectively.
Keywords: Outcome-based Education; Open-ended Laboratory; Post-covid-19; Engineering Education; perceptions; Online-lab